IL-21/IL-21R Regulates the Neutrophil-Mediated Pathologic Immune Response during Chlamydial Respiratory Infection - Zeng, Jiajia; Xu, Yueyue; Tan, Lu; Zha, Xiaoyu; Yang, Shuaini; Zhang, Hong; Tuo, Yuqing; Sun, Ruoyuan; Niu, Wenhao; Pang, Gaoju; Sun, Lida; Bai, Hong (Mediators of Inflammation, 2022)
IL-21/IL-21R was documented to participate in the regulation of multiple infection and inflammation. During Chlamydia muridarum (C. muridarum) respiratory infection, our previous study had revealed that the absence of this signal induced enhanced resistance to infection with higher protective Th1/Th17 immune responses. Here, we use the murine model of C. muridarum respiratory infection and IL-21R deficient mice to further identify a novel role of IL-21/IL-21R in neutrophilic inflammation. Resistant IL-21R-/- mice showed impaired neutrophil recruitment to the site of infection. In the absence of IL-21/IL-21R, pulmonary neutrophils also exhibited reduced activation status, including lower CD64 expression, MPO activity, and neutrophil-produced protein production. These results correlated well with the decrease of neutrophil-related chemokines (KC and MIP-2), inflammatory cytokines (IL-6, IL-1β, and TNF-α), and TLR/MyD88 pathway mediators (TLR2, TLR4, and MyD88) in infected lungs of IL-21R-/- mice than normal mice. Complementarily, decreased pulmonary neutrophil infiltration, activity, and levels of neutrophilic chemotactic factors and TLR/MyD88 signal in infected lungs can be corrected by rIL-21 administration. These results revealed that IL-21/IL-21R may aggravate the neutrophil inflammation through regulating TLR/MyD88 signal pathway during chlamydial respiratory infection.